STRATEGI PEMBELAJARAN PRAKARYA BIDANG KERAJINAN DI SMA PEMBANGUNAN LAB. UNP - Helmi Helmi; Ernis Ernis (Serupa The Journal of Art Education, 2020)
The purpose of this research is to describe learning strategies, learning methods and craft learning media in the field of crafts in SMA Pembangunan Lab. UNP. This type of research is descriptive with a qualitative approach to collecting observation data. interview and documentation. Based on the results of research on craft learning strategies in the field of craft in the Lab Development High School. UNP can be concluded that in the implementation of learning strategies, methods and learning media. The teacher carries out the learning process well. and also the methods and media used in accordance with the recommendations of the 2013 curriculum.Keywords: Learning Strategies, Learning Methods, Learning Media